Negotiator Behavior and the Occurence of Disputes - Ashenfelter, Orley; Currie, Janet (American Economic Review, 1990)
It is generally recognized that possible gains from cooperation are not always realized because negotiating parties sometimes fail to reach agreement. Such negotiation failures are ex post inefficient and have long defied economist's attempts to explain them. In this paper we discuss breakdowns in collective bargaining when disputes are resolved by compulsory arbitration. We argue that the study of arbitration offers insights into the nature of negotiation failures which may be of general interest.(This abstract was borrowed from another version of this item.)